Fabrication of porous fibrous alumina ceramics by direct coagulation casting combined with 3D printing. Issue 5 (1st April 2018) - Chen, An-Nan; Wu, Jia-Min; Liu, Yu-Xuan; Liu, Rong-Zhen; Cheng, Li-Jin; Huo, Wen-Long; Shi, Yu-Sheng; Li, Chen-Hui
Abstract: A novel forming method for preparing porous alumina ceramics using alumina fibers as raw materials by direct coagulation casting (DCC) combined with 3D printing was proposed. Porous fibrous alumina ceramics were fabricated through temperature induced coagulation of aqueous-based DCC process using sodium tripolyphosphate (STPP) as dispersant and adding K2 SO4 as removable sintering additives. The sacrificial coated sand molds was fabricated by 3D printing technology, followed by the infiltration of silica sol solution for the subsequent suspension casting. Stable alumina suspension of 40 vol% solid loading was obtained by adding 2.0 wt% STPP and 40 wt% K2 SO4 . The controlled coagulation of the suspension could be realized after heating at 90 °C for about 35 min. The ceramic sample sintered at 1450 °C for 2 h showed the highest compressive strength of 24.33 MPa with porosity of 57.38%. All samples sintered at 1300–1450 °C had uniform pore size distributions with average pore size of 7.2 µm, which indicated the good structure stability when sintered at high temperature.